INDIGO DALAM NOVEL SUPERNOVA AKAR KARYA DEE LESTARI: KAJIAN PSIKOLOGI SASTRA - Erna Rakhmawati (EDU-KATA, 2020)
The background of this research is many indigo events in the community and many indigo literary works. Indigo research in the “Indigo dalam Novel Supernova Akar Karya Dee Lestari:Tinjauan Psikologi Sastra,” first aims to find the description of the indigo abilities experienced by the characters, secodly to find the causes of indigo experienced by characters, and thirdly to find out the type of indigo experienced by characters in the Supernova Akar. The research includes qualitative descriptive research on data analysis techniques using textual analysis or text analysis. The subject of this study is a character in the Supernova Akar. The result of research that is narated by Dee lestari source are; 1)levitasi, 2) procegnition, 30 psicometri, 4) teleportasi, and 5) clayvoyance. Indigo causes experienced by characters in the Supernova Akar are; 1) a gift from God, 2) from offspring, and from training. The type of indigo experienced by characters in the Supernova Akar are; humanis and artis.